Cytospora species from Populus and Salix in China with C. davidiana sp. nov. Issue 5 (May 2015) - Wang, Yan-Li; Lu, Quan; Decock, Cony; Li, Yong-Xia; Zhang, Xing-Yao
Abstract: Poplar and willow plantations have become widespread in China, in order to meet national economic and environmental needs. The emergence of several pathogens is enhanced by climatic change and associated human factors. Species of Cytospora are well-known pathogens on poplar and willow, and cause stem cankers and diebacks. In the present study, we conducted a survey of Cytospora species occurring on Populus spp. and Salix spp. in China. We used morphological examination and phylogenetic inferences, based on the DNA sequence data from the internal transcribed spacer regions (ITS1, 5.8S rDNA, and ITS2) and partial β-tubulin gene, to identify six Cytospora species occurring on poplar and willow. Five of these species belonged to known taxa, viz . Cytospora chrysosperma (asexual state of Valsa sordida ), Cytospora translucens (asexual state of Leucostoma translucens ), Cytospora fugax (asexual state of Valsa salicina ), Cytospora atrocirrhata, and Cytospora kantschavelii . Our study yielded a new species, Cytospora davidiana sp. nov., on poplar. The new species is characterized by typical torsellioid conidiomata. An additional Cytospora sp. 1, which formed a distinct clade in the phylogenetic inferences, remains unnamed; the paucity of available materials prevented phenotypical characterization. Highlights: Cytospora canker is a main threat to enormous poplar and willow plantations in China. Species diversity of genus Cytospora infecting Poplar and Salix are illustrated. One new species within Cytospora is discovered and described.